2019
DOI: 10.1101/813303
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of initial microbial biomass abundance on respiration during pine litter decomposition

Abstract: 25Microbial biomass is increasingly used to predict respiration in soil organic carbon (SOC) 26 models. Its increased use combined with the difficulty of accurately measuring this variable 27 points a need to directly assess the importance of microbial biomass abundance for carbon (C) 28 cycling. To test the hypothesis that the initial microbial biomass abundance (i.e. biomass 29 abundance on new plant litter) is a strong driver of plant litter C cycling, we manipulated 30 biomass abundance by 10 and 100-fo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 68 publications
(60 reference statements)
0
14
0
Order By: Relevance
“…During the combination step, suspensions from pine litter microcosms were filtered with a 40-μm filter to remove pine litter. We did not attempt to standardize the biomass of these inocula, as previous work with pine litter microcosms has demonstrated that effects of initial differences in microbial biomass on ecosystem functioning are minimal after a 30-day incubation ( 85 ). For R2A invader inocula, the microbial abundance of each was roughly estimated using optical density (OD) measurements, and the communities were diluted to a common OD measurement.…”
Section: Methodsmentioning
confidence: 99%
“…During the combination step, suspensions from pine litter microcosms were filtered with a 40-μm filter to remove pine litter. We did not attempt to standardize the biomass of these inocula, as previous work with pine litter microcosms has demonstrated that effects of initial differences in microbial biomass on ecosystem functioning are minimal after a 30-day incubation ( 85 ). For R2A invader inocula, the microbial abundance of each was roughly estimated using optical density (OD) measurements, and the communities were diluted to a common OD measurement.…”
Section: Methodsmentioning
confidence: 99%
“…We hypothesized that initial community size ( i.e, bacterial biomass per g soil) would influence community dynamics in response to C addition, and that variation in soil DNA content might explain variation in community dynamics with respect to land use type. Bacterial biomass varies significantly in relation to land-use intensity (Nsabimana et al ., 2004; Fornasier et al ., 2014; Zhang et al ., 2016; Albright et al ., 2020). We used DNA yield as a proxy for microbial biomass, since soil DNA yield correlates strongly with soil microbial biomass and with cell numbers (Blagodatskaya et al ., 2003; Joergensen and Emmerling, 2006; Blagodatskaya and Kuzyakov, 2013; Fornasier et al ., 2014; Spohn et al ., 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The SFA is also using SOMic to improve data interpretation [7]. A strength of SOMic is that it can be applied to gain insight into microbial dynamics and soil carbon cycling at many scales,…”
Section: What Are the Consequences Of Microbial Community Functional mentioning
confidence: 99%
“…Litter-derived fraction of SOC ranging from days in simple laboratory microcosms [7] to the decades at the global scale [6]. We used SOMic to assess if differences in the quantity of microbial biomass added to laboratory microcosms could be a substantial factor in the large variation in carbon flow observed among communities decomposing plant litter over a short (6-week) timescale [7].…”
Section: Time (Days)mentioning
confidence: 99%
See 1 more Smart Citation